META-ANALYSIS OF THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON CRITICAL THINKING SKILLS - Fitri, Aidina Milla; Mufit, Fatni (Journal of Learning and Technology in Physics, 2024)
This study aims to analyze the effect of the Problem Based Learning (PBL) learning model in improving critical thinking skills, the influence of PBL in education labels and subject matter. This research compares the PBL learning model with the conventional one. This research is a meta-analysis study. By finding the effect size value. The average value of the effect size or critical thinking skills was 0.52 in the medium category. At the level of education, it is more effective learning materials on Optical instruments material at the high school education level. The conclusion of this research is that Problem Based Learning can improve critical thinking and problem solving skills.Keywords: Problem Based Learning and Critical Thinking